2023
DOI: 10.3390/ijms241310770
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Lactate Dehydrogenase A Inhibitor Oxamate Reduces Experimental Osteoarthritis and Nociception in Rats via Possible Alteration of Glycolysis-Related Protein Expression in Cartilage Tissue

Abstract: Osteoarthritis (OA) is the most common form of arthritis and joint disorder worldwide. Metabolic reprogramming of osteoarthritic chondrocytes from oxidative phosphorylation to glycolysis results in the accumulation of lactate from glycolytic metabolite pyruvate by lactate dehydrogenase A (LDHA), leading to cartilage degeneration. In the present study, we investigated the protective effects of the intra-articular administration of oxamate (LDHA inhibitor) against OA development and glycolysis-related protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…These findings suggest that metabolic reprogramming plays a pivotal role in the proinflammatory effect observed in bFLS induced by both D-lactate and TNFα. In addition, the intra-articular administration of oxamate, acting as an LDHA inhibitor, in a murine osteoarthritis model demonstrated reduced pain and inflammation, alongside an improvement in metabolic reprogramming [ 59 ]. Moreover, it has been demonstrated that knocking down HIF-1α in RA-FLS led to a reduction in LDHA and phosphofructokinase expression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that metabolic reprogramming plays a pivotal role in the proinflammatory effect observed in bFLS induced by both D-lactate and TNFα. In addition, the intra-articular administration of oxamate, acting as an LDHA inhibitor, in a murine osteoarthritis model demonstrated reduced pain and inflammation, alongside an improvement in metabolic reprogramming [ 59 ]. Moreover, it has been demonstrated that knocking down HIF-1α in RA-FLS led to a reduction in LDHA and phosphofructokinase expression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is supported that the glycolytic pathway or some of its key proteins can regulate chondrocyte apoptosis in the course of OA. The LDHA inhibitor oxalate has been shown to reduce chondrocyte apoptosis in articular cartilage of the experimental osteoarthritis rat model by possibly altering the expression of glycolysis-related proteins ( 154 ). Dexamethasone has been found to increase ROS levels and inhibit monocarboxylate transporter 4 (MCT4), leading to apoptosis caused by lactate accumulation ( 136 ).…”
Section: The Regulated Programmed Cell Death and Glycolysismentioning
confidence: 99%